Assessment of renal size based on patient’s position during ultrasound scanning - Sanadi, Nurul Najmi; Ahmad Zaiki, Farah Wahida (International Islamic University Malaysia, 2018)
Introduction: The purpose of the study was to assess the size for both kidneys based on the position of patient during ultrasonography examination. Normal renal size measurement is very important to evaluate in determining a healthy kidney. Method: Thirty volunteers, consist of 15 males and 15 females were involved in this study. The patients were scanned in supine, oblique, and prone position. The readings were repeated for three times for each position. Results: The mean length of kidney in supine, oblique and prone were 99.03 mm, 96.32 mm and 95.94 mm, respectively. Meanwhile, the mean width of kidney were 44.30 mm, 44.31 mm and 46.65 mm, respectively. The renal length measurement in prone position was statistically significant with p = 0.023 (p < 0.05), while the renal width measurement in oblique and prone position were statistically significant with p = 0.006 and p = 0.009 respectively. Conclusion: This research emphasised the importance of investigating the different types of position of patient during the ultrasound scanning. The importance mentioned were the reduction of scanning time for patient and cost- effectiveness of the procedures. Besides, it also gave accurate result for the renal measurement.